(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study looked into the problems secondary school teachers face and how they deal with these problems in schools across Sri Lanka. It focused on two main questions: What challenges do teachers face in managing classrooms in secondary schools? And what strategies do they use to handle these challenges? To find answers, the researcher collected data from 200 teachers. These teachers were randomly selected from secondary schools in the Colombo and Jayawardenepura Education Zones. The questionnaire, designed with a four-point modified Likert scale, was validated and its reliability confirmed using Cronbach’s Alpha, which produced a reliability coefficient of 0.81. Quantitative data were analyzed using SPSS software, while qualitative data were examined through thematic analysis. The data collected was analyzed using mean and z-test statistical methods. The analysis of the data showed that secondary school teachers in Colombo and Jayewardenapura are facing various classroom management challenges. These issues include student indiscipline, lack of adequate teaching resources, and overcrowded classrooms. However, the study also identified a number of practical strategies that, if effectively implemented, could help teachers manage and overcome these difficulties. To achieve meaningful change, there is a strong need for collaborative efforts among key stakeholders. The Ministry of Education, parents, community leaders, and students must work hand in hand with teachers. Such cooperation can lead to better classroom environments, improved student behavior, and overall enhanced teaching and learning experiences. Addressing these challenges collectively will significantly contribute to the reduction, and possible elimination, of classroom management problems in secondary schools.